Light-induced enhancement of quantum dot photovoltaic devices with nitrogen doped titanium oxide capping layers - Yu, Jialin; Xia, Jilin; Kim, Inho; French, Benjamin L.; Haverinen, Hanna M.; Alford, T. L.; Jabbour, Ghassan E. (ELSEVIER, 2013)
For the first time it is reported that nitrogen-doped titanium oxide with light annealing can improve the device performance by 300% when acting as an interfacial layer between CdSe quantum dot/poly-3-hexylthiophene and the cathode in the photovoltaic devices. Substitutional N doping with a concentration of 1.2 at.% was found by X-ray photoelectron spectroscopy which was responsible for 0.1 eV band gap reduction of TiOx. Photoluminescence and the external quantum efficiency spectrum confirmed the enhanced charge collection and association rate after light annealing. Three-dimensional atomic force microscopy results agreed with the series resistance measurements, confirming that a good contact was achieved. The topography study also indicated that the active layer morphology changed upon light annealing. Improved stability and longer lifetime were also found with TiOxNy capped devices, which were optimized with light annealing. TiOx capped devices were also evaluated for comparison in this study. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: TIO2; ABSORPTION; FILMS; WATER